2013
DOI: 10.1177/0748233713500822
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metal contents in spices and herbs from Saudi Arabia

Abstract: In the recent years, there has been a growing interest in monitoring heavy metal contamination of spices/herbs. Spices and herbs are sources of many bioactive compounds that can improve the tastes of food as well as influence digestion and metabolism processes. In the present study, the levels of some essential and toxic elements such as iron (Fe), zinc (Zn), copper (Cu), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), lead (Pb), and cadmium (Cd), present in common spices/herbs that were purchased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 60 publications
5
23
9
Order By: Relevance
“…Li intake of a 70 kg adult averagely between 0.65 and 3.1 mg/day (Schrauzer, 2002). The current results did not exceed the recom- In the case of toxic elements ( (Seddigi et al, 2016;Sherif et al, 1980). The content of Hg (0.96 mg/kg) was reported by Ndelekwute et al, (2014) which was higher than the present study.…”
Section: Elemental Compositioncontrasting
confidence: 70%
“…Li intake of a 70 kg adult averagely between 0.65 and 3.1 mg/day (Schrauzer, 2002). The current results did not exceed the recom- In the case of toxic elements ( (Seddigi et al, 2016;Sherif et al, 1980). The content of Hg (0.96 mg/kg) was reported by Ndelekwute et al, (2014) which was higher than the present study.…”
Section: Elemental Compositioncontrasting
confidence: 70%
“…The Vietnamese sample was found to have more abundance of nutritious elements among the three samples tested. Similar reports with high nutritious values have been reported previously for BP samples (Al‐Jasass & Al‐Jasser, ; Seddigi, Kandhro, Shah, Danish, & Soylak, ). The instrumental and physicochemical analyses revealed that the Vietnamese sample has a comparatively good quality in terms of extract yield, ash values, and nutritious value of elements present, except the amount of PPN, which was found to be greater in the Pakistani sample.…”
Section: Discussionsupporting
confidence: 90%
“…The author observed that spice grinding in commercial mills can lead to the incorporation of 3 to 5 times more Fe, due to the wear of the grinding equipment used in this process. High levels of Fe have also been reported by De La Calle et al 20 (1264 ± 216 mg kg -1 ), Jawad 21 (481.28 ± 2.37 mg kg -1 ), Karadaş et al 19 (158 ± 19 mg kg -1 ), Matloob 8 (194.1 ± 39.03 mg kg -1 ), Özcan et al 17 (89.24 ± 11.43 mg kg -1 ), Seddigi et al 7 (144 ± 9.2 mg kg -1 ), Singh and Garg 14 (76.0 mg kg -1 ), Soliman 25 (620.02 ± 541.36 mg kg -1 ) and Soylak et al 12 (281.8 ± 20.5 mg kg -1 ).…”
Section: Discussionsupporting
confidence: 54%
“…6 In this context, the number of studies aiming at the determination of trace elements in plant samples, such as spices, herbs and medicinal plants, including black pepper, has increased in recent years. [5][6][7][8][9][10][11][12][13][14][15][16] Different analytical procedures have been reported in the literature for the determination of trace elements in pepper. Özcan et al 17 reported the determination of 18 elements in black pepper samples after acid decomposition using inductively coupled plasma optical emission spectrometry (ICP OES).…”
Section: Introductionmentioning
confidence: 99%